2019
DOI: 10.1088/1361-6595/ab4170
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoplasmadynamic two-stage micro-cathode arc thruster for CubeSats

Abstract: The addition of the acceleration stage to a micro-cathode vacuum arc thruster (μCAT) increases the thrust and the specific impulse. This improves the control of small satellites' orbital parameters and, therefore, the overall efficiency of this thruster for CubeSats. In this article, we show that the second accelerating stage based on the magnetoplasmadynamic (MPD) approach allows improvements not only to the thrust (almost twice, from 9 to 18 μN), but the thrust-to-power ratio (in 53%, from 3.2 to 4.9 μN W −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…An additional source of ion acceleration comes from the Lorentz force F L ~ j θ × B r , which contributes to thrust at higher values of the magnetic field in the vicinity of the discharge region and discharge currents (and, correspondingly, electron currents in plasma). Previous simulations of the contribution of F L to thrust ( 11 ) showed that the j θ × B r acceleration region has a typical length of within 1 mm; thus, the contribution of Lorentz force to thrust can be comparable with the initial thrust ( 25 ) and strongly depends on the magnetic field strength and configuration defined by the position of the magnet with respect to the discharge area.…”
Section: Discussionmentioning
confidence: 99%
“…An additional source of ion acceleration comes from the Lorentz force F L ~ j θ × B r , which contributes to thrust at higher values of the magnetic field in the vicinity of the discharge region and discharge currents (and, correspondingly, electron currents in plasma). Previous simulations of the contribution of F L to thrust ( 11 ) showed that the j θ × B r acceleration region has a typical length of within 1 mm; thus, the contribution of Lorentz force to thrust can be comparable with the initial thrust ( 25 ) and strongly depends on the magnetic field strength and configuration defined by the position of the magnet with respect to the discharge area.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results for the µCAT-MPD thruster with a pulsed magnetic field formed by the coil with an iron core [22] demonstrated that the thrust increase strongly depends on the coil current as well as the power depositing in the second stage. However, for the case of pulsed magnetic coil, the latter parameter cannot be easily varied and predicted due to the changeable degree of magnetization of plasma electrons during the pulse.…”
Section: Introductionmentioning
confidence: 96%
“…However, for the case of pulsed magnetic coil, the latter parameter cannot be easily varied and predicted due to the changeable degree of magnetization of plasma electrons during the pulse. Therefore, by setting a power in the second stage less than that in the first stage, as it was achieved in [22], the thrust grows quite moderately (from 3-9 µN up to 15-18 µN) with a moderate thrust to power ratio (around 4 µN W −1 ). A permanent magnet has an advantage by giving a stable configuration of magnetic field without consuming electrical energy and independently from the thruster firing regime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional typical μCAT was coaxial, which was constituted by a cylindrical inner cathode, an inner insulating sleeve (IIS) and a cylindrical outer anode [3,4], and is denoted as CA s -µCAT, where the foot mark 's' indicates a single insulating sleeve, in this research work. To improve the propulsion performance of a μCAT, some research works have already been conducted [5][6][7]. However, almost all of the current μCAT structures provided thrust by mainly using the directional ejected plasma jet formed near the cathode during operation, where the anode just acted as a collector of charged particles from the cathode.…”
Section: Introductionmentioning
confidence: 99%